2017
DOI: 10.1136/bmjopen-2016-014077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of socioeconomic factors on cardiovascular-related symptoms among residents in Fukushima after the Great East Japan Earthquake: a cross-sectional study using data from the Fukushima Health Management Survey

Abstract: ObjectiveTo investigate the association between socioeconomic factors and the exacerbation of cardiovascular symptoms among evacuees after the Great East Japan Earthquake.MethodsA sample of 73 433 individuals was included in the Fukushima Health Management Survey. Self-report questionnaires were used to determine the influence of socioeconomic factors including living arrangements, loss of employment and decreased income on the exacerbation of headache, dizziness, palpitations and shortness of breath. Odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The evacuees experienced not only the earthquake itself but also a tsunami and/or the indirect effects of a nuclear power plant accident. These disasters and experiences affected their living environment, relatives and friends, and socioeconomic status [15,16]. There were also some changes seen between the pre-and post-disaster phases in lifestyle status among evacuees; for example, smoking, drinking, and physical activities [17] as well as psychological distress [18].…”
Section: Introductionmentioning
confidence: 99%
“…The evacuees experienced not only the earthquake itself but also a tsunami and/or the indirect effects of a nuclear power plant accident. These disasters and experiences affected their living environment, relatives and friends, and socioeconomic status [15,16]. There were also some changes seen between the pre-and post-disaster phases in lifestyle status among evacuees; for example, smoking, drinking, and physical activities [17] as well as psychological distress [18].…”
Section: Introductionmentioning
confidence: 99%
“…By promoting health management to change people's lifestyles, it has been shown that the mortality rate of cardiovascular diseases and diabetes mellitus in China has been reduced [21][22]. Moreover, the cost of healthcare can be effectively controlled by investing in health management.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported that the disaster was followed by cases of serious posttraumatic stress disorder (PTSD), which in turn induced CVD in certain individuals affected by the disaster [13,14]. According to evidence from a few studies, various modifiable risk factors for CVD in addition to psychological factors have been identified, one of which is evacuation status [15][16][17]. After a disaster, the resulting traumatic events and evacuation status affect individuals' lifestyle and psychological state [18,19].…”
Section: Introductionmentioning
confidence: 99%